Assessment of the capacity building in Comprehensive Agricultural Support Programme (CASP) funded projects in Capricorn District of Limpopo Province, South Africa - Magadani, Thivhavhudzi Benert (University of Limpopo, 2014)
Capacity building is a process of building capabilities in individuals, groups, institutions, organisations, and societies at the local, national and international levels, to be more effectively prepared for and respond to public health threats of a crisis in a sustainable manner. This process is designed to reinforce or create strengths upon which communities can mitigate vulnerabilities as a result of emergencies and disasters. The main aim of the study was to assess capacity building in Comprehensive Agricultural Support Programme (CASP) funded projects in Capricorn District of Limpopo Province. The CASP programme was initiated to provide post-settlement support for farmers who have benefitted from the Land Reform programmes. Since zfthe inception of this programme, there has not been any assessment of capacity building as one of the pillars of CASP. The objective of the study was to assess capacity building on productivity and to determine the impact of capacity building on the CASP funded projects. The study hypothesed that an increase in the level of productivity of CASP funded projects depends on the level of capacity building. The term training refers to the acquisition of knowledge, skills and competencies as a result of the teaching of vocational or practical skills. In land reform projects, training is provided as the planned and organised activity of a consultant to impart skills, techniques and methodologies to employers and their employees, to assist them in establishing and maintaining employment and a place of employment that is safe and healthy. The Farmer training is offered in two different methods, viz., on-farm and off-farm training. The on-farm training involves a service-provider visiting the farmer and rendering the training at the farm, whereas the off-farm training requires a farmer to go to the planned venue or institution of training to receive the planned training. iv
Thesis (M.Dev.) --University of Limpopo, 2014
Keywords: Capacity building; Projects; 338.18008968; Agricultural development projects -- South Africa